2010
DOI: 10.4149/gpb_2010_02_113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one-day reperfusion after transient forebrain ischemia on circulatory system in the rat

Abstract: Abstract. Although ischemia/reperfusion injury remains incompletely understood, it appears that reactive oxygen species produced mainly during postischemic recirculation play a critical role. The present study examined the impact of forebrain ischemia and subsequent one-day reperfusion on several blood parameters. We determined glutamate concentration in whole blood, measured Cu/Zn-and Mn-SOD (superoxide dismutase) activity in blood cells as well as plasma, and investigated the prevalence of single and double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As a first in the present experiment, we tested the hypothesis that production of the factor‐inducing tolerance of neuronal cells to ischemia depends on protein synthesis. Our previous results confirmed the rapid response of sensitive brain tissue to nutrients and oxygen insufficiency in the systemic circulation (Kravcukova et al ., , ). We observed that global as well as focal brain ischemia led to dramatic changes in several blood parameters, such as the activity of SOD enzymes and glutamate level in early postischemic reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As a first in the present experiment, we tested the hypothesis that production of the factor‐inducing tolerance of neuronal cells to ischemia depends on protein synthesis. Our previous results confirmed the rapid response of sensitive brain tissue to nutrients and oxygen insufficiency in the systemic circulation (Kravcukova et al ., , ). We observed that global as well as focal brain ischemia led to dramatic changes in several blood parameters, such as the activity of SOD enzymes and glutamate level in early postischemic reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue excitotoxicity reaches beyond the border of the central nervous system. In the blood, the early stage of post-ischaemic reperfusion reflects an increase in blood glutamate level, ultimately gaining in oxidative stress and affecting the enzyme antioxidant defence [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work we observed changes of some biochemical parameters in blood in model of global (Kravcukova et al 2009(Kravcukova et al , 2010 as well as focal ischemia (unpublished data) that are clearly expressed mainly in early period of postischemic recirculation. Based on this we decided to study ischemia impact on blood BDNF during blood supply restriction and early reperfusion and examine its effect on whole blood, plasma and blood cells.…”
mentioning
confidence: 99%